Avaliação microbiológica das principais hortaliças comercializadas nosmunicípios de Juazeiro do Norte e Crato, no Ceará - Saraiva, Cleopatra do Nascimento (Universidade Federal Rural do Semi-Árido, 2013)
Aiming to evaluate the microbiological contamination of vegetables sold in Crato and Juazeiro do Norte cities, Ceará, from May to August, 2011, analyzes of total and fecal coliforms were performed on 184 vegetable samples, collected in outdoor markets, supermarkets and produce stores, from conventional and organic farming. Two collects were made on different months in each store or stand visited. From the total collected, 90 samples (60 from conventional farming and 30 from organic farming) were from lettuce (Lactuca sativa L.) and 94 (84 from conventional farming and 10 from organic farming) were from tomato (Lycopersiconesculentum Mill.). Of 144 samples from conventional farming and 40 from organic farming collected, 23,61% and 50%, respectively, were presented nonstandard for fecal coliforms. The lettuce presented a sample percentual unsuitable for human consumption higher than tomato samples in both farming methods. From the places mentioned by the merchants as vegetables growers, the city of Jardim CE obtained the highest frequency of lettuce unsuitable samples (65,31%) and Juazeiro da Bahia BA obtained the highest frequency of tomato unsuitable samples (40%). The vegetables sold in Juazeiro do Norte CE and Crato CE were contaminated by total and fecal coliforms, and from 23,95% of analyzed samples the level of fecal coliform contamination were above the levels allowed by Brazilian legislation
Microbiological evaluation of the main vegetables sold in the cities of Juazeiro do Norte and Crato, Ceará
Keywords: Lactuca sativa L.; Lycopersiconesculentum Mill; Microbiologicalcontamination; fecal coliforms; Lactuca sativa L.; Lycopersiconesculentum Mill; Contaminação microbiológica; Coliformes fecais; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA